How can we improve the diagnosis and management of bladder pain syndrome? Part 2:ICI‐RS 2018. (10th December 2019) - Khullar, Vik; Digesu, G. Alessandro; Veit‐Rubin, Nikolaus; Sahai, Arun; Rahnama'i, Mohammad Sajjad; Tarcan, Tufan; Chermansky, Christopher; Dmochowski, Roger
Abstract: Background: This paper summarises the discussion in a think tank at the International Consultation on Incontinence‐Research Society (ICI‐RS) 2018 about the treatment of bladder pain syndrome. Aims: To review the treatments of bladder pain syndrome from behavioural treatments to surgical interventions. Materials and Methods: Review the literature in the light of the think tank discussions. Results: All guidelines recommend different levels of treatment starting with conservative behavioral treatments then introducing oral treatments followed by intravesical instillations. If these treatments fail then more invasive treatments such as botulinum toxin injections, neuromodulation, or surgery could be suggested. Conclusion: Unfortunately for all treatments, the numbers are limited and, therefore, the evidence base is not strong. Further suggestions for research are suggested.